Identifying the environmental conditions that determine the distribution of an endangered estuarine fish to manage risk of entrainment - Hamilton, Scott A.; Murphy, Dennis D.; Montoya, Eduardo L. (Frontiers in Ecology and Evolution, 2025)
Allocation of scarce water resources to meet beneficial but competing end uses has become commonplace in drought-stricken western North America. In the Sacramento-San Joaquin Delta in California, regulatory agencies endeavor to protect the endemic and imperiled delta smelt from entrainment at water-project pumps, while meeting critical water deliveries to agriculture and urban users. The current water management strategy is not effective at or efficient in meeting those dual goals. To improve current management practices, we develop a risk-based strategy that protects delta smelt from population-level impacts from water-project pumping, while enhancing essential water deliveries to consumers. We identify and quantify the environmental factors associated with the presence of delta smelt in the vicinity of water-project pumps. Essential in this process is the identification of “precedent” factor conditions that contribute to determining the distribution of delta smelt. When delta smelt are likely not near the pumps in the south Delta, the risk of entrainment is low, allowing for water deliveries to be increased with de minimis losses of delta smelt. We present predictive management-guidance models that identify the environmental-factor conditions influencing rates of take for three delta smelt life stages. In a simulation for a 22-year period of water-project operations, the implementation of a risk-based strategy keeps losses of delta smelt under specified limits in all years, while increasing water deliveries by an average of more than 250,000 acre-feet (306,000 ML) per year. The models allow resource managers to identify in real time the ecological circumstances that signal impending heightened risks to delta smelt, thereby triggering appropriate conservation responses.